Tổng hợp, phân tích cấu trúc và tính chất phổ một số aryloxiaxetylhiđrazon của carvon - Công, Nguyễn Tiến; Sơn, Trần Quốc; Hiến, Lê Văn; Hoài Thu, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
Ten aryloxyacetylhydrazones of carvone have been synthesized. Their structures have been confirmed by IR, 1H-NMR, 13C-NMR, DEPT and mass spectra. The spectral data has been investigated